Association of Body Mass Index With the Use of Health Care Resources in Low-Risk Nulliparous Pregnancies After 39 Weeks of Gestation. Issue 5 (5th May 2022) - Costantine, Maged M.; Sandoval, Grecio J.; Grobman, William A.; Reddy, Uma M.; Tita, Alan T.N.; Silver, Robert M.; El-Sayed, Yasser Y.; Wapner, Ronald J.; Rouse, Dwight J.; Saade, George R.; Thorp, John M.; Chauhan, Suneet P.; et al.
Abstract : Among nulliparous low-risk pregnant people, higher body mass index was associated with longer time from admission to delivery, total hospital length of stay, and more frequent utilization of intrapartum and postpartum health care resources. Abstract : OBJECTIVE: To compare health care medical resource utilization in low-risk nulliparous pregnancies according to body mass index (BMI, calculated as weight in kilograms divided by height in meters squared) categories. METHODS: This is a secondary analysis of a multicenter randomized controlled trial of induction of labor between 39 0/7 39 and 4/7 weeks of gestation compared with expectant management in low-risk nulliparous pregnant people, defined as those without standard obstetric indications for delivery at 39 weeks. Body mass index at randomization was categorized into four groups (lower than 25, 25–29, 30–39, and 40 or higher). The primary outcome of this analysis was time spent in the labor and delivery department from admission to delivery. Secondary outcomes included length of stay (LOS) postdelivery, total hospital LOS, and antepartum, intrapartum, and postpartum resource utilization, which were defined a priori. Multivariable generalized linear modeling and logistic regressions were performed, and 99% CIs were calculated. RESULTS: A total of 6, 058 pregnant people were included in the analysis; 640 (10.6%) had BMIs of lower than 25, 2, 222 (36.7%) had BMIs between 25 and 29, 2, 577 (42.5%) had BMIs of 30–39, and 619 (10.2%) had BMIs of 40 or higher. Time spent in the labor and delivery department increased from 15.1±9.2 hours for people with BMIs of lower than 25 to 23.5±13.6 hours for people with BMIs of 40 or higher, and every 5-unit increase in BMI was associated with an average 9.8% increase in time spent in the labor and delivery department (adjusted estimate per 5-unit increase in BMI 1.10, 99% CI 1.08–1.11). Increasing BMI was not associated with an increase in antepartum resource utilization, except for blood tests and urinalysis. However, increasing BMI was associated with higher odds of intrapartum resource utilization, longer total hospital LOS, and postpartum resource utilization. For example, every 5-unit increase in BMI was associated with an increase of 26.1% in the odds of antibiotic administration, 57.6% in placement of intrauterine pressure catheter, 5.1% in total inpatient LOS, 31.0 in postpartum emergency department visit, and 23.9% in postpartum hospital admission. CONCLUSION: Among low-risk nulliparous people, higher BMI was associated with longer time from admission to delivery, total hospital LOS, and more frequent utilization of intrapartum and postpartum resources. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, NCT01990612.